THU0201 Weak Correlation between A Multi-Biomarker Disease Activity Score and Clinical Response with Baricitinib in A Phase 2b Study in Rheumatoid Arthritis. (15th July 2016) - Fleischmann, R.; Genovese, M.; Keystone, E.; Weinblatt, M.; Rancourt, J.; Nantz, E.; Schlichting, D.; Zuckerman, S.; Macias, W.L.; Taylor, P.
Abstract : Background: Regular disease activity assessment should be a key component of rheumatoid arthritis (RA) care. In patients with moderate-to-severe RA and inadequate response to methotrexate (MTX-IR) treated with baricitinib (bari) 1, 2, 4, or 8 mg in a Phase 2b double-blind study, bari demonstrated clinically and statistically significant improvements at 12 wks including DAS28-CRP <2.6 for 1 (14%), 2 (15%), 4 (37%), and 8 (22%) mg versus placebo (4%; PBO). 1 (Elevated high-sensitivity C-reactive protein (hsCRP) >1.2xULN or erythrocyte sedimentation rate (ESR) >28 mm/h was required at study entry. 1 ) In the same study, only modest, statistically significant improvements in a multi-biomarker disease activity score (MBDA) 2 were observed. 3 Objectives: To investigate how MBDA correlates with clinical endpoints in the previously reported study. 3 Methods: Post-hoc statistical analysis was conducted on combined bari 1, 2, 4, and 8 mg (n=189) and paired low (1, 2 mg; n=91) and high (4, 8 mg; n=98) doses using partial correlation analyses, which controls for effects of association with other variables, to assess the relationship between MBDA and absolute change from baseline in 13 disease activity measures. Results: Mean MBDA improved from baseline to Wk 12 for each dose versus PBO, 3 but the two highest correlations were only of moderate strength: hsCRP [a component of MBDA] (r=0.60) and DAS28-CRP (r=0.43). For all other measures, associations with MBDA were significant (p<0.05) but of weak magnitude; swollen joint count (SJC) was not significant (Table). The low- and high-dose pairs had mostly weak correlations (not shown); the strongest correlation was with hsCRP (r=0.50, 0.68, respectively; both p<0.001). Conclusions: In MTX-IR patients treated with bari for 12 wks, significant changes in clinical response measures were seen but were not strongly correlated with MBDA. The highest correlations, although statistically significant, were of moderate strength. MBDA score changes did not have a strong correlation to clinical measures with bari. If these observations are corroborated they would suggest that caution is required when assessing clinical response to bari using the MBDA. References: Keystone E et al. Ann Rheum Dis 2015;74(2):333–340. Segurado OG, Sasso EH. Clin Exp Rheumatol 2014;32(85):S29-S34. Taylor P et al. Ann Rheum Dis 2015;74(Suppl 2):257–258 as presented at EULAR 2015. Disclosure of Interest: R. Fleischmann Grant/research support from: Eli Lilly and Company, Pfizer, Consultant for: Eli Lilly and Company, Pfizer, M. Genovese Grant/research support from: AbbVie, Astellas, Eli Lilly and Company, Galapagos, Pfizer, Vertex, Consultant for: AbbVie, Astellas, Crescendo Bioscience, Eli Lilly and Company, Galapagos, Pfizer, Vertex, E. Keystone Grant/research support from: Abbott Laboratories, Amgen Inc., AstraZeneca Pharmaceuticals LP, Bristol-Myers Squibb, Eli Lilly and Company, F. Hoffmann-La Roche Inc, Janssen Inc, Novartis Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, UCB, Consultant for: Abbott Laboratories, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Eli Lilly and Company, F. Hoffmann-La Roche Inc, Genentech Inc, Janssen Inc, Merck, Pfizer Pharmaceuticals, UCB, Speakers bureau: Abbott Laboratories, Astrazeneca LP, Bristol-Myers Squibb Canada, F. Hoffmann-La Roche Inc., Janssen Inc., Pfizer Pharmaceuticals, UCB, Amgen, M. Weinblatt Grant/research support from: Crescendo Bioscience, Consultant for: Eli Lilly and Company, Pfizer, AbbVie, Crescendo Bioscience, J. Rancourt Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, E. Nantz Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, D. Schlichting Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Zuckerman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, W. Macias Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Taylor Grant/research support from: Celgene, GlaxoSmithKline, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly and Company, Galapagos, GlaxoSmithKline, Merck, Pfizer, Takeda, USB